REFLECTIONS ON BEING A LANGUAGE EDUCATOR IN BRAZIL AND THE UNITED STATES: WHY RACIAL IDENTITIES ALWAYS MATTER - Jorge, Miriam (Cadernos de Linguagem e Sociedade, 2022)
This paper aims at sharing some perspectives on being a language educator in Brazil and the United States. My main focus is on racialized learning and teaching experiences and how they may shape our praxis in language studies. The concept of intersectionality (Crenshaw, 1989) is fundamental to my discussion, framed around three main threads: race, language, and class. I use autoethnography as a process and a method for reflection on my experiences concerning what I see from my transnational lenses. The discussion explores how racialized experiences matter in two contexts that are so similar yet so different.